Durable Ultraflexible Organic Photovoltaics with Novel Metal‐Oxide‐Free Cathode. (19th December 2018) - Jiang, Zhi; Fukuda, Kenjiro; Huang, Wenchao; Park, Sungjun; Nur, Roda; Nayeem, Md. Osman Goni; Yu, Kilho; Inoue, Daishi; Saito, Masahiko; Kimura, Hiroki; Yokota, Tomoyuki; Umezu, Shinjiro; et al.
Abstract: Flexible and stretchable organic photovoltaics (OPVs) are promising as a power source for wearable devices with multifunctions ranging from sensing to locomotion. Achieving mechanical robustness and high power conversion efficiency for ultraflexible OPVs is essential for their successful application. However, it is challenging to simultaneously achieve these features by the difficulty to maintain stable performance under a microscale bending radius. Ultraflexible OPVs are proposed by employing a novel metal‐oxide‐free cathode that consists of a printed ultrathin metallic transparent electrode and an organic electron transport layer to achieve high electron‐collecting capabilities and mechanical robustness. In fact, the proposed ultraflexible OPV achieves a power conversion efficiency of 9.7% and durability with 74% efficiency retention after 500 cycles of deformation at 37% compression through buckling. The proposed approach can be applied to active layers with different morphologies, thus suggesting its universality and potential for high‐performance ultraflexible OPV devices. Abstract : Ultraflexible organic photovoltaics are developed by employing a novel metal‐oxide‐free cathode that consists of a printed ultrathin metallic transparent electrode and an organic electron transport layer. The proposed ultraflexible organic photovoltaics achieve a power conversion efficiency of 9.7% and durability with 74% efficiency retention after 500 cycles of deformation at 37% compression through buckling.